Observation of NOy uptake by particles in the arctic tropopause region at low temperatures - Feigl, C.; Schlager, H.; Ziereis, H.; Curtis, J.; Arnold, F.; Schiller, C. (Geophysical Research Letters, 1999)
Measurements pf gas- and condensed-phase NOy, HNO3, O-3, and particle concentration and size were performed on 24 January 1997 during POLSTAR on a flight through an ice cloud. In the ice cloud below the tropopause only 2 to 4 pptv particle NOy were detected. The observed average mixing ratio of total HNO3 is significantly larger than the detected particle NOy. Considering the combined error limits of the NOy and KNO3 measurements, however, it cannot be ruled out that the observed uptake of NOy was limited by the available gas-phase HNO3. The ratio of total HNO3 to gaseous NOy measured during the cirrus cloud penetration amounts only to 0.2 in contrast to 0.9 in the stratospheric part of the flight.